Neural oscillations: sustained rhythms or transient burst-events? - Van Ede, F; Quinn, A; Woolrich, M; Nobre, A (Cell Press, 2018)
Frequency-specific patterns of neural activity are increasingly interpreted as transient bursts of isolated events rather than as rhythmically sustained oscillations. This has potentially far-reaching implications for theories of how such oscillations originate and how they shape neural computations. As this debate unfolds, we explore alternative interpretations and ask how best to distinguish between them.